2008
DOI: 10.1016/j.prevetmed.2008.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of packed cell volume as an indicator of trypanosomal infections in cattle in eastern Zambia

Abstract: In this study, packed cell volume-values (PCV) are evaluated as indicator of trypanosomiasis infections in cattle. A total of 734 blood samples were collected in 11 different sampling sites in eastern Zambia: 84 calves (<1 year), 52 young females and 40 young males (between 1 and 3 years), 228 cows, 317 oxen and 13 bulls (>3 years). All samples were subjected to three diagnostic tests: parasitological examination using the buffy coat method, PCR/RFLP and PCV determination. The results were compared and analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 15 publications
6
53
4
Order By: Relevance
“…Such significant difference of PCV values in infected and non-infected cattle had been reported by several workers [26][27][28]. They demonstrated that haematocrit values of infected cattle decreased during the infection period.…”
Section: Tc = T Congolense Tv = T Vivax T Bb = T Brucei Brusupporting
confidence: 76%
“…Such significant difference of PCV values in infected and non-infected cattle had been reported by several workers [26][27][28]. They demonstrated that haematocrit values of infected cattle decreased during the infection period.…”
Section: Tc = T Congolense Tv = T Vivax T Bb = T Brucei Brusupporting
confidence: 76%
“…This value of 26% constitutes a threshold that is a valuable indicator of trypanosomal infections when associated with the parasitological results (Marcotty et al, 2008). The low proportion of anaemic animals is a strong signal that treatments are effective in this area and that the health condition of the animals can be maintained even in the presence of the parasites and their vectors.…”
Section: Serological Prevalencementioning
confidence: 99%
“…This could be explained by the effects of climate change and anthropogenic actions on natural resources in the area in recent years that have contributed to the current transformation of tsetse ecology for their survival (Dao et al al., 2008;. This could be added to the diagnostic method used in the study which is less sensitive than the PCR technique using parasite-specific primers which is more sensitive and allows to have higher prevalences (Desquesnes et al, 1999;Marcotty et al, 2008).…”
Section: Discussionmentioning
confidence: 99%